Changes in sleep habits and knowledge after an educational sleep program in 12th grade students. Issue 3 (23rd April 2013) - Sousa, Ivanise Cortez; Souza, Jane Carla; Louzada, Fernando Mazzilli; Azevedo, Carolina Virginia Macêdo
Abstract: The objective of this research was to evaluate the effect of an education program using the meaningful learning approach on sleep knowledge and habits of 12th grade students. Thirty‐four student volunteers (aged 16.8 ± 0.6 years) were divided into intervention (Sleep Education Program – SEP) and control groups. Sleep knowledge and habits were assessed by the "health and sleep" questionnaire. Also, the students filled out a sleep diary and the Karolinska Sleepiness Scale by one week (Stage 1). These procedures were repeated 3 weeks after the SEP (Stage 2) that was evaluated by a questionnaire. The SEP consisted of five 50‐minute classes to discuss the physiological and behavioral processes of sleep and healthy lifestyle. At Stage 2, the intervention group increased the percentage of correct responses in 63% of the questions. On weekdays, they increased time in bed by 26 min, woke up 11 min later and showed a tendency to go to bed 18 min earlier ( P = 0.07). On weekends, they advanced bedtime and wake‐up times. These changes were associated with decreased irregularity at bedtimes and wake up times. These results were not observed in the control group, except the advance on wake up time on weekends. The frequency and duration of naps and daytime sleepiness levels did not differ between the stages for both groups. The SEP increased knowledge and contributed to positive changes in the adolescents' sleep‐wake cycle (SWC). However, daytime sleepiness levels remained unchanged probably due to an insufficient reduction on sleep deprivation to decrease its negative consequences.